Europeanisation of VET : the Spanish Vocational Education and Training system and the influence of European education policy - Zaunstöck, Tim [Verfasser]; Marhuenda Fluixá, Fernando [Verfasser]; Ros-Garrido, Alicia [Verfasser]; Fischer, Martin [Verfasser] (My University, 2021)
"The paper discusses the development of Spanish Vocational Education and Training (VET) over the past four decades and the extent to which and ways in which joining the European Economic Communities in 1986 contributed to the transformation of Spain’s VET system. The paper is structured in five sections: the justification of our choice of Europeanisation as a theoretical approach, a presentation of the system prior to accession into the European Union (EU), a description of the European VET policy defined in the Bruges-Copenhagen process, and an examination of changes in the Spanish VET at the turn of the century. The relations between the European and Spanish VET policies are then discussed in view of Europeanisation theory, particularly considering their specification in terms of the National Qualification Framework approved in 2002 and the European Qualification Framework (EQF) established in 2008 to examine adaptation and accommodation. The paper finishes by discussing how top-down and bottom-up trends based on the theory of Europeanisation have resulted in the current Spanish VET system adhering to its own national identity while converging with European recommendations." (Author's abstract ; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; 370; Berufsbildungssystem; Spanien; europäische Integration; Historische Entwicklung; EU-Beitritt; EU-Bildungspolitik